Concomitant exposure to vitamin C and E inhibited monosodium glutamate - induced ovarian toxicity in female rats - Wiwin Rohmawati; Yuni Istiananingsih; Nurdiana Nurdiana; Wisnu Barlianto; Pande Made Dwijayasa (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: Our study aimed to investigate the combinatorial effect of vitamin C and E on oxidative stress, the number of folicles, and hormonal level in female rats orally exposed to monosodium glutamate (MSG). Materials and Methods:Female, twelve weeks old Wistar rats ingested with of MSG at dose 140 mg/200 gram body weight (bw) with or without combination of vitamin C and E. Twenty five rats were divided into five group (n = 5 each), control group, MSG-treatment group, MSG-treatment + 0.2 mg/g bw vitamin C + 0.04 IU/g bw vitamin E (MSG + CE1), MSG-treatment + 0.4 mg/g bw vitamin C + 0.04 IU/g bw vitamin E (MSG + CE2), and MSG-treatment + 0.6 mg/g bw vitamin C + 0.04 IU/g bw vitamin E (MSG + CE1). Analysis of malondialdehyde (MDA) level was done colorimetrically. Analysis of the number of ovarian follicles was done histopathologically with hematoxylin eosin staining. Analysis of 17beta-estradiol and follicle stimulating hormone (FSH) levels were done by ELISA technique. Results: There were significantly (P < 0.05) increased ovarium MDA levels and atresia follicle number in groups exposed to MSG compared to non-exposure group. The level of FSH, 17beta-estradiol, the number of primary, secondary, de Graaf follicles were significantly lower in MSG-treatment group compared to control group (P < 0.05). The administration of combined vitamin C and E (second and third dose) significantly (P < 0.05) decreased the MDA levels and the number of atresia follicle compared to the MSG-exposed groups, to reach level in control group (P > 0.05). MSG + CE2 and MSG + CE3 significantly increased FSH level, number of primary follicles, compared to MSG-treatment group (P < 0.05), to reach similar level in control group (P > 0.05). All dose of combined vitamin C and E significantly increased 17beta-estradiol level and the number of secondary and de Graaf follicles compared to MSG-treatment group (P < 0.05), to reach significantly higher level compared to control group (P < 0.05). Conclusion: The present data suggest that combination of vitamin C and E as in this study inhibited ovarium toxicity caused by MSG treatment. [Cukurova Med J 2014; 39(3.000): 517-524]